Three-dimensional numerical study of the deep western boundary current in the South China Sea - Zhou, Muping; Ling, Zheng; Chen, Changlin (Frontiers in Marine Science, 2024)
This study utilized a three-dimensional ocean general circulation model to investigate the intensity, thickness, and width of the three-dimensional deep western boundary current (DWBC) in the South China Sea (SCS). The numerical results show that the DWBC begins near the inlet of the Luzon overflow, flows westward along the northern boundary, proceeds southward along the western boundary, and ultimately terminates at the southern boundary. The mean DWBC's velocity, thickness, and width is 4.78 cm/s, 1645 m, and 140 km, respectively. Combined with the dynamic results, it is evident that the three-dimensional structure of the DWBC appears to have been visibly weakened after the closure of the deep Luzon overflow. Strong deep mixing has a significantly stronger, thicker, and wider effect on the intensity, thickness, and width of the DWBC. Both the bottom and lateral friction coefficients negatively impact the DWBC in the SCS.